AI 2015: advances in artificial intelligence : 28th Australasian Joint Conference, Canberra, ACT, Australia, November 30 - December 4, 2015 : proceedings /: 28th Australasian Joint Conference, Canberra, ACT, Australia, November 30 - December 4, 2015 : proceedings. (2015) - Unknown
No abstract available